Fuzzy intelligent control method for improving flight attitude stability of plant protection quadrotor UAV - He, Zhihui; Gao, Wanlin; He, Xiongkui; Wang, Minjuan; Liu, Yunling; Song, Yue; An, Zewu (International Journal of Agricultural and Biological Engineering, 2019)
At present, the attitude control method of plant protection UAV is the classical PID control, but there are some imperfections in the PID control, such as the contradiction between speediness and overshoot, the weak anti-jamming ability and adaptability. The physical parameters of plant protection UAV are time-varying, and the airflow also interferes with it. The control ability of classical PID is limited, and its control parameters are fixed, and its anti-jamming ability and adaptability are not strong. Therefore, a fuzzy adaptive PID controller is proposed in this paper. Fuzzy logic control is used to optimize the control parameters of PID in order to improve the dynamic and static performance and adaptability of attitude control of plant protection UAV. In the process of research, the mathematical model of UAV is established firstly, then the fuzzy adaptive PID is designed, and then the simulation is carried out in Simulink. The simulation results show that the fuzzy adaptive PID controller has better dynamic and static control performance and adaptability than the traditional PID controller. Therefore, the proposed control method has excellent application value in the attitude of plant protection UAV.Keywords: quadrotor UAV, attitude control, plant protect, fuzzy adaptive PID, SimulinkDOI: 10.25165/j.ijabe.20191206.5108Citation: He Z H, Gao W L, He X K, Wang M J, Liu Y L, Song Y, et al. Fuzzy intelligent control method for improving flight attitude stability of plant protection quadrotor UAV. Int J Agric & Biol Eng, 2019; 12(6): 110–115.